Evaluation of Cash on Delivery System for Improving Legal Certainty in the Development Of Electronic Transactions In Indonesia - Aqil, Nabil Abduh; Putri, Chelsea Mutiara; Yunisa, Dinda (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2022)
Online transactions using the Cash On Delivery (COD) payment method play an important role in increasing the intensity of electronic transactions in Indonesia, this is because the COD payment method can reach consumers who do not have bank accounts or other digital wallets. The increase in the use of this payment method is inversely proportional to the public's perception of misguided understanding of the COD payment method, resulting in new problems such as consumers who are reluctant to pay for goods that have been ordered to protests accompanied by threats to delivery couriers. This paper aims to examine the weaknesses in COD transactions so that evaluations can be carried out in order to increase legal certainty for all parties. The type of research used is normative juridical using the statutory and conceptual approach. This study uses secondary data as the main data and uses library research as a material collection technique. All materials that have been collected are then inventoried, classified, and analyzed using descriptive analysis which aims to describe the problem so that innovative solutions are obtained. There are several shortcomings in this COD method, such as: buyer's misconception of the COD system, disinformation of goods with real conditions, and complicated methods of purchasing goods. This deficiency can be overcome in several scenarios, namely: strengthening legal protection for couriers delivering goods, using the principle of strict liability and reversing the burden of proof (reversion of the burden of proof) in the protection of E-Commerce consumers, and simplifying the rules for returning goods.